Developing Worksheets Using Engineering Design Process to Promote Sustainable Development Goals for Pre-service Physics Teacher - Atin Nuryadin; Nurul Sulaeman; Lambang Subagiyo; Muhammad Sholeh; Eko Andrianto (Universitas Lambung Mangkurat, 2023)
This research aims to design a worksheet using the Engineering Design Process (EDP) model to promote Sustainable Development Goals (SDGs) that are appropriate for pre-service physics teachers. The specific objectives of this study are to describe the validity of the worksheet and explore the pre-service physics teacher's response to the worksheet. The research design is research and development (R&D) with a model of analysis, design, development, implementation, and evaluation (ADDIE). The participants in this study were 45 pre-service science teachers. The research instruments are the worksheet validation sheet and the response questionnaire. The results show that the worksheet is categorized as very feasible. In addition, based on the pre-service physics teachers' responses, the worksheet is in a good category. It can be concluded that the developed worksheet using the EDP model is appropriate for learning.